Identifying Human Naïve Pluripotent Stem Cells − Evaluating State‐Specific Reporter Lines and Cell‐Surface Markers. (25th March 2018) - Collier, Amanda J.; Rugg‐Gunn, Peter J.
Abstract : Recent reports that human pluripotent stem cells can be captured in a spectrum of states with variable properties has prompted a re‐evaluation of how pluripotency is acquired and stabilised. The latest additions to the stem cell hierarchy open up opportunities for understanding human development, reprogramming, and cell state transitions more generally. Many of the new cell lines have been collectively termed 'naïve' human pluripotent stem cells to distinguish them from the conventional 'primed' cells. Here, several transcriptional and epigenetic hallmarks of human pluripotent states in the recently described cell lines are reviewed and evaluated. Methods to derive and identify human naïve pluripotent stem cells are also discussed, with a focus on the uses and future developments of state‐specific reporter cell lines and cell‐surface proteins. Finally, opportunities and uncertainties in naïve stem cell biology are highlighted, and the current limitations of human naïve pluripotent stem cells considered, particularly in the context of differentiation. Abstract : Human pluripotent stem cells captured in a spectrum of states presents a challenge for unambiguously defining cell types. We review molecular hallmarks of human pluripotent states and evaluate methods to identify naïve pluripotent cells, with a focus on the uses and future developments of reporter cell lines and cell‐surface proteins.